Perancangan Media Promosi Geomorfologi Karst Rammang-rammang Berbasis alam Sebagai Identitas Kabupaten Maros Sulawesi Selatan - Poetri, Indah Andini; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of the design media promotion Karst Rammang-rammang is to make Rammang-rammang as the leading tourist visit in South Sulawesi that has the charm of the natural beauty that is not owned by the other regions. Research done by qualitative methods apply by doing interviews, documentation, observation and study of the library to get the data that used in the creation of design concepts as supporters of media promotion. The concept of the research is